(untitled) - Kirkwood, Kenneth P. (Rutland, Vt., 1970)
This book is of interest to a wide circle: to specialists of Japanese history; to students of the relations between the modern West and contemporary non-Western civilizations; and to inquirers into the general nature of human society.
Keywords: Civilization, modern,Renaissance; 17th century; Japan